Management of a case of thromboembolism post spine surgery: a case report - Tomer, Manoj K. S.; Shah, Kalpana; Bhojraj, Shilpa; Devi, Pinki (International Journal of Research in Medical Sciences, 2021)
Postoperative deep vein thrombosis (DVT) of lower limbs is often asymptomatic. In many patients, fatal pulmonary embolism (PE) is the first clinical manifestation of postoperative venous thromboembolism (VTE). Routine screening for asymptomatic DVT of the lower limbs has a low sensitivity and is quite impractical. For these reasons, routine and systematic prophylaxis in patients at risk, is the strategy of choice to reduce the burden of VTE after surgery. If used appropriately such prophylaxis is cost effective since it reduces the incidence of symptomatic thromboembolic events, which require costly diagnostic procedures and prolonged anticoagulation therapy. Here we report the post-operative course of a spine surgery patient, presenting with DVT in calf veins, which lodged into pulmonary artery and was managed successfully with low molecular weight heparin (LMWH), embolectomy, inferior vena cava (IVC) filter, and dabigatran.